Dietary patterns and child, parental, and societal factors associated with being overweight and obesity in Vietnamese children living in Ho Chi Minh city - Thi My Thien Mai; Quoc Cuong Tran; Smita Nambiar; Danielle Gallegos; Jolieke C. Van der Pols (Wiley, 2024)
Abstract Childhood overweight and obesity are rapidly increasing in urban Vietnam. Dietary patterns are understudied for their association with obesity risk in these children, and it is unclear which parental and societal factors should be targeted in prevention efforts. The study assessed child characteristics, dietary patterns, parental and societal factors for associations with childhood overweight and obesity status in Ho Chi Minh City, Vietnam. A sample of 221 children aged 9-11 years was randomly selected from four Ho Chi Minh City primary schools. Weight, height and waist circumference were measured using standardized methods. Three 24‐h dietary recalls were collected from 124 children, which were used to assess dietary patterns using principal component analysis (PCA). Parents completed a questionnaire about child, parental and societal factors. The overall prevalence of obesity was 31.7% and of combined overweight and obesity 59.3%. Three main dietary patterns from 10 food groups were identified by PCA: traditional (grains, vegetables, meat and meat alternatives), discretionary (snacks and sweetened beverages), and industrialized (fast food and processed meat). Children with higher discretionary diet scores had higher odds of being overweight. Being a boy, screen time over 2 h/day, parental underestimation of child weight status, father's obesity, and household income in the lowest quintile were positively associated with childhood obesity. Future intervention programmes in Vietnam need to consider targeting children's unhealthy diets and parental perceptions of child weight status, as well as focusing on upstream approaches that reduce inequities contributing to childhood obesity and concomitant dietary patterns.